UPAYA MENURUNKAN TINGKAT KECACATAN PRODUK PSST SLICE MUSHROOMS 4 OZ DENGAN METODE FMEA (FAILURE MODE AND EFFECT ANALYSIS) DI PT. ETR PURWODADI - Masfufah; Munir, Misbach (Journal Knowledge Industrial Engineering (JKIE), 2019)
ETR is an agroindustrial company that manufactures button mushrooms (champignon) in cans with a production capacity of 25 kg of fresh button mushrooms every day in a variety of styles and sizes in cans or glass. The Company experienced a product defect by 70.13% on products PSST Slice Mushrooms 4 Oz, so it requires prevention efforts to reduce the level of product defects that occur. This study used descriptive qualitative method for mendeskriptifkan results of the analysis method FMEA (Failure Mode and Effect Analysis). FMEA is a method of systematic and structured manner can analyze and identify the result or consequence of a failure of the system or process, and reduce or analyze the probability of failure. The results showed three types of product defects PSST Slice Mushrooms 4 Oz namely defect labeling, defect secondary packaging, defect products and primary packaging defects of the most influential is the defect label (fumble, labels upside down, torn, engaged, gross, the label does not fit, loose ). The results of the analysis using FMEA (Failure Mode and Effect Analysis) showed a decrease in the value of the RPN (Risk Priority Number) after an improvement by fishbone diagram, where the value of RPN before repair of 378-20 and after repair value of the RPN fell to 120-2 with sense the results showed a decrease in the level of disability products PSST Slice Mushrooms 4 Oz.